Design and implementation of a multi-DOF hand and basic motions for rope-knotting tasks. (19th May 2022) - Takizawa, Masaru; Kudoh, Shunsuke; Suehiro, Takashi
Abstract : For complex tasks such as tying a knot, simply creating a robot hand with many degrees of freedom is insufficient. It is also important to extract the requirements of the task, design the hand based on these requirements, and implement functions to use the hand effectively. Thus, in this study, we have designed a robot hand with three fingers each having three degrees of freedom and developed basic functions to realize rope-knotting tasks. In experiments, the designed robot hand and functions were applied to performing various manipulations during rope-knotting tasks, and the redundancy provided by the structure could be utilized to generate motions. GRAPHICAL ABSTRACT: UF0001